Representasi Konflik Ayah dan Anak melalui Komunikasi Interpersonal dalam Film Ngeri-Ngeri Sedap - Hartini Agaluh; Mareta Puri Rahastine; Anggie Ayu Astria Latuperissa (Kajian Administrasi Publik dan ilmu Komunikasi, 2026)
This study aims to analyze the representation of father-child conflict through interpersonal communication in the film Ngeri-Ngeri Sedap using Stuart Hall's theory of representation. This research employed a descriptive qualitative method within a constructivist paradigm. The analysis was conducted using the constructionist approach. Data were collected through non-participant observation and documentation of scenes, dialogues, and interactions among the characters in the film. The findings reveal that the conflict is represented through differences in life choices, lack of openness in communication, and clashes between paternal authority and children's freedom to determine their own future. The conflicts are represented through dialogues, sarcasm, defensive attitudes, and power relations within the family influenced by Batak cultural values. The study also indicates that ineffective interpersonal communication reinforces family conflict and affects the relationship between fathers and their children. Through Stuart Hall's theory of representation, Ngeri-Ngeri Sedap highlights the importance of openness, empathy, mutual understanding, and respect for each family member's life choices in building harmonious family relationships. Therefore, this study concludes that the representation of conflict in the film not only portrays differences in perspectives between fathers and children but also demonstrates how cultural values shape interpersonal communication patterns and conflict resolution within the family.